Trajectories of depressive symptoms and risk of chronic liver disease: evidence from CHARLS - Xikun Yang; Jiangping Ma; Hui Li (BMC Gastroenterology)
Abstract Background It is unclear whether there is a association between the long-term depressive symptoms and chronic liver disease(CLD). The aim of present study was to investigate the relationship between the trajectories of depressive symptoms and CLD in middle-aged and older Chinese adults. Methods The study included data from 7351 Chinese individuals, which from the China Health and Retirement Longitudinal Study (CHARLS). Latent Class Growth Model (LCGM) and Growth Mixture Model (GMM) identified five categories of depressive symptom trajectories from 2011 to 2015. Multiple logistic regression models were used to analyze the relationship between depressive symptom trajectories and CLD in 2015–2020. Results We identified five distinct trajectories of depressive symptoms characterized by persistent low CES-D scores throughout follow-up (low-stable; 4621 cases [62.86%]); high starting CES-D scores but then declining (high-decreasing; 824 cases [11.21%]); persistent high CES-D scores during follow-up (high-stable; 508 cases [6.91%]); starting moderate CES-D scores but then increasing (moderate-increasing; 844 cases [11.48%]); and low starting CES-D scores that increased and then remitted through follow-up (remitting; 554 cases [7.54%]). A total of 420 (5.71%) participants developed chronic liver disease during follow-up. The ORs (95% CI) for the risk of developing chronic liver disease in participants on the moderate-increasing trajectory, high-decreasing trajectory, and high-stable trajectory were 1.44 (1.05–1.93), 1.59 (1.17–2.12), and 2.25 (1.62–3.08), respectively, compared with participants on the low-stable trajectory. Conclusion In Chinese middle-aged and older adults, individuals with moderate-increasing, high-decreasing, and high-stable trajectories of depressive symptoms over time had an increased risk of developing CLD.